2009
DOI: 10.1111/j.1469-8137.2009.02956.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genetic loci for zinc uptake and distribution in barley (Hordeum vulgare)

Abstract: Summary• Micronutrient malnutrition, often called 'hidden hunger', affects over two billion people globally. This is particularly problematic in developing countries where widespread zinc (Zn) deficiency exists as a result of a predominantly plant-based diet. Furthermore, supplemental fertilizers are often unavailable or unaffordable in impoverished regions where soil infertility is common. Delivery of more Zn via food grains is theoretically possible through selective breeding strategies, but severe technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 41 publications
4
54
0
Order By: Relevance
“…Schlegel et al (1998) pointed out that chromosomes L1, L4 and L7 of Agropyron intermedium and chromosomes V2 and V7 of Haynaldia villosa have the effects on enhancing of Zn efficiency. In barley, genes that control grain Zn concentrations are located on chromosomes 2H and 5H (Lonergan et al 2009). Distelfeld et al (2007), Uauy et al (2006) and Waters et al (2009) reported that the Gpc-B1 (TtNAM-B1) gene which are located on 6BS, are involved in more efficient remobilization of Zn and Fe from leaves to grain.…”
Section: Discussionmentioning
confidence: 99%
“…Schlegel et al (1998) pointed out that chromosomes L1, L4 and L7 of Agropyron intermedium and chromosomes V2 and V7 of Haynaldia villosa have the effects on enhancing of Zn efficiency. In barley, genes that control grain Zn concentrations are located on chromosomes 2H and 5H (Lonergan et al 2009). Distelfeld et al (2007), Uauy et al (2006) and Waters et al (2009) reported that the Gpc-B1 (TtNAM-B1) gene which are located on 6BS, are involved in more efficient remobilization of Zn and Fe from leaves to grain.…”
Section: Discussionmentioning
confidence: 99%
“…However, zinc (Zn) deficiency in rice has been widely reported in many rice-growing regions of the world (Lonergan et al, 2009;Tiong et al, 2014). Zn deficiency in crop plants results in not only yield reduction but also Zn malnutrition in humans, where a high proportion of rice is consumed as a staple food (Wu et al, 2011;Chasapis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Further work at ICRISAT is in progress to identify genetically diverse germplasm (noniniary type) from the recently constituted pearl millet mini-core collection (Upadhyaya et al 2010) for developing hybrid parental lines with high seed-Fe concentration. In a two-rowed barley, the pooling of three most favourable QTL alleles increased seed-Zn content and concentration by an average of 53% and 75%, respectively (Lonergan et al 2009). The AgroSalud project (www.AgroSalud.org), a consortium of centers from the CGIAR, NARS, Universities, and NGOs formed in 2005 with funding support from Canadian International Development Agency (CIDA), aims to improve food and nutrition security among vulnerable populations living in 14 Latin American and Caribbean countries through nutritionally enhanced biofortified crops (beans, maize, rice, sweet potato) and food products derived from these crops and cassava.…”
Section: E Developing Seed Iron-and Zinc-dense Cultivars Usingmentioning
confidence: 99%
“…Other QTL were identified on LG B3, B6, B7, and B9 for zinc and B4, B6, B7, and B8 for iron Blair et al 2009a Fe: 11 QTLs on six LGs, 8%-36% variation; Zn: 11 QTLs on four LGs, 9%-39% variation; a QTL on LG B1 (nearest to fin marker) accounted 34% variation for Fe and Zn, while another QTL on LG B6 (nearest to AGAT05 marker) accounted 36%-39% variation for Fe and Zn Cichy et al 2009 A locus on LG9 associated with Zn accumulation Gelin et al 2007 Two QTL for Fe (25% variation) and one QTL for Zn (15% variation) (Stangoulis et al 2007). In Barley, specific markers have been developed for a high zinc QTL on chromosome 2H (Sadeghzadeh et al 2010), while other QTLs have been identified by Lonergan et al (2009). Iron reductases are members of the protein super-family of flavocytochromes and function in roots to convert Fe from a plant unavailable form (ferric, Fe 3þ ) to an available form (ferrous, Fe 2þ ) that can be readily absorbed (Grusak 1995).…”
Section: Total Of Nine Seed Mineral Qtl Were Identified In An Andeanmentioning
confidence: 99%
See 1 more Smart Citation